A typology of internationally qualified dentists in the United Kingdom - Latha S Davda; David R Radford; Sasha Scambler; Jennifer E Gallagher (Elsevier, 2024)
Introduction: The Global Strategy for Human Resources for Health 2030, requires member states to half their dependency on an international workforce by 2030. In order to design policies towards that goal, country-specific research on migration motivations of the health workforce is required. The United Kingdom (UK) is a net importer of health professionals and whilst there is a body of research on doctors' and nurses' migration, there is no research on the migration motivations of migrant dentists in the UK. This research explored the migration motivations of internationally qualified dentists (IQDs) in the UK and presents a typology to understand the global migration of dentists in the context of oral health workforce. Methods: The paper presents qualitative data from semi-structured interviews conducted between August 2014 and October 2017, of IQDs working in the United Kingdom. The topic guide for interviews was informed by the literature, with new themes added inductively. A phenomenological approach involving an epistemological stance of interpretivism, was used with framework analysis. Results: A total of 38 internationally qualified dentists (M = 18, F = 20), migrating from the five World Health Organization regions, and working in general practice, NHS hospitals and in community dental services across the four nations of the UK were interviewed. Seven types of internationally qualified dentists were identified working in the UK. They were livelihood migrants, career-orientated migrants, dependant migrants, backpacker migrants, commuter migrants, undocumented migrants, and education-tourist migrant. The categories were based on their migration motivations, which were complex, multifactorial, and included personal, professional, national, and international drivers. The typology, based on their migration motivations, offered a structured, comprehensive understanding of the migrant dental workforce. This typology involving dentists provides additional dimensions to commuter and undocumented migrants described in the context of other health professionals. The education-tourist migrant is a new category proposed as an extension to existing typology in health professional migration. Conclusions: The typology of internationally qualified dentists has congruency with other health professionals' typology in categories previously described and demonstrates that each of these categories are complex, fluid and change in response to policy changes. The new category of education-tourist migrant along with oral health dimensions of commuter and undocumented migrants adds to the existing typology in health professional migration.